2015
DOI: 10.18052/www.scipress.com/ilcpa.59.170
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Sulfamerazine and Sulfamethazine to Bovine Serum Albumin and Nitrogen Purine Base Adenine: A Comparative Study

Abstract: ABSTRACT. Quenching of bovine serum albumin (BSA) and DNA base (adenine) by sulfamerazine (SM) and sulfamethazine (SMT) was studied using UV-visible, fluorescence cyclic voltammetry and molecular docking methods. A strong fluorescence quenching reaction of SM and SMT to BSA/adenine was observed and the quenching mechanism was suggested as static. Both drugs can bind to BSA and adenine with stoichiometric ratio of 1:1 and the protein -drug complexes are stabilized mainly by hydrogen bonds and van der Waals inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The drop of the voltammetric reduction current in the presence of BSA/adenine may be attributed to slow diffusion of the BSA/adenine binding with TCA drugs. The results also specified that interactions between drugs and BSA/adenine happened in the reaction and that the electrode process was irreversible .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The drop of the voltammetric reduction current in the presence of BSA/adenine may be attributed to slow diffusion of the BSA/adenine binding with TCA drugs. The results also specified that interactions between drugs and BSA/adenine happened in the reaction and that the electrode process was irreversible .…”
Section: Resultsmentioning
confidence: 89%
“…There was no marked UV–visible spectral shift observed in BSA and adenine when varying the drug concentration, except a decrease in the absorption maxima. The changes in the absorption spectra indicated that there was interaction of the TCA drugs with BSA and adenine to form protein–drug complexes .…”
Section: Resultsmentioning
confidence: 99%
“…The population size was set to 150. During the search, a translational step of 0.2 Å, and quaternion and torsion steps of 5 were applied [20][21][22][23][24][25].…”
Section: Autodockmentioning
confidence: 99%
“…In general, when a small molecule interacts with biomolecules changes in absorbance and in the position of the band should occur [20][21][22][23][24][25][26]. If the binding mode is intercalation, the π* orbital of the intercalated molecule can couple with the π orbital of the biomolecules base pairs, thus, decreasing the π → π* transition energy and resulting in the bathochromism.…”
Section: Absorption Spectral Studymentioning
confidence: 99%
See 1 more Smart Citation